Hubungan Tingkat pengetahuan Gizi, Asupan Gizi dan Status Gizi pada atlet di Sekolah Sepak Bola Samkot Samarinda Tahun 2022 - Akshan, Achmad; Ratnawati, Ratnawati; Reski, Sepsina (JGK: Jurnal Gizi dan Kesehatan, 2022)
Background: Athletes' nutritional knowledge has a very important role in choosing the right food and drink. Nutrition plays a role in the success of a team. However, most of the athletes' nutritional intake is not appropriate due to the lack of knowledge and understanding of athletes in choosing food. Nutritional status is also needed to maintain the degree of fitness and health, to help growth to support the achievement of athletes. Purpose : This study aims to determine the relationship between nutritional knowledge and nutritional intake with nutritional status of athletes at the Samkot Samarinda football school. Methods : This research is a cross sectional study design. The research was conducted in March 2022. There were 50 respondents in this study. Data on age, weight and height from anthropometric measurements. Knowledge data from the knowledge questionnaire and food intake from the food recall questionnaire. Nutritional status data from BMI/U calculations and classified based on PMK No 02 of 2020. Result : The results show that there is no significant relationship between knowledge and nutritional status with p value (P> 0.39), then there is no significant relationship between energy intake (P> 0.82), protein intake (P> 0.75) , fat intake (P> 0.82) and carbohydrate intake (P> 0.07) with the nutritional status of athletes. Consclusion : There is no significant relationship between nutritional knowledge and nutritional intake with nutritional status in athletes at the Samkot Samarinda football school.